Patterns of Referral to Radiation Oncology among Patients with Bladder Cancer: a Population-based Study. Issue 3 (March 2017) - Quirt, J.S.; Siemens, D.R.; Zaza, K.; Mackillop, W.J.; Booth, C.M.
Abstract: Aims: Radical radiotherapy is a reasonable alternative to cystectomy for some patients with invasive bladder cancer, and postoperative radiotherapy may be indicated in patients at high risk of local recurrence. Here we describe pre- and postoperative radiation oncology consultation among patients with bladder cancer in Ontario. Materials and methods: Records of radiotherapy and surgery were linked to the Ontario Cancer Registry (OCR) to identify all patients who received treatment with curative intent for bladder cancer between 1994 and 2008. Billing records were linked to the OCR to determine which patients were seen by radiation oncology before radical therapy or after cystectomy. Factors associated with radiation oncology consultation were explored by logistic regression. Results: In total, 5259 patients with bladder cancer underwent treatment with curative intent in Ontario between 1994 and 2008. Of these, 3879 had primary cystectomy and 1380 had primary radiotherapy. Thirty-two per cent (1698/5259) of all patients were seen by radiation oncology. Independent factors associated with radiation oncology consultation included advanced age ( P < 0.001), greater comorbidity ( P < 0.001) and earlier year of diagnosis ( P < 0.001). Rates also varied widely across geographical regions (range 20–57%); this variation was highly significant on multivariate analysis ( P < 0.001). Only 10% (370/3759) of patients with cystectomy had a preoperative radiation oncology consultation. Ten per cent of patients treated by cystectomy (386/3879) were seen by radiation oncology in the postoperative setting; rates varied widely across regions (range 6–44%). These geographical variations were highly significant in the multivariate analysis ( P < 0.001), which also showed that younger patients, those with higher stage (pT or pN), and those with positive margins, were more likely to have a postoperative radiation oncology consultation (all P < 0.001). Only 19% (80/420) of cases with positive margins had a postoperative radiation oncology consultation. Conclusions: One third of all patients with muscle-invasive bladder cancer in routine practice were seen in consultation by radiation oncology. Few patients who undergo cystectomy have the benefit of either a preoperative or a postoperative opinion about the potential role of radiotherapy in their management. Closer collaboration between radiation oncologists and urologists is warranted. Highlights: Guidelines support either cystectomy or radiotherapy for invasive bladder cancer. This population-based study describes referral patterns to radiation oncology. One third of patients with bladder cancer were referred to radiation oncology. Only 10% of patients were seen by radiation oncology postoperatively. Closer collaboration between radiation oncology and urology is warranted.